Medical Data Analysis Meets Artificial Intelligence (AI) and Internet of Medical Things (IoMT) - Manoj Diwakar; Prabhishek Singh; Vinayakumar Ravi (Bioengineering, 2023)
AI is a contemporary methodology rooted in the field of computer science [...]